Bank lending and monetary policy: the effects of structural shift in interest rates - Goh, K.L.; Yong, S.L. (Economics Bulletin, 2007)
This paper provides evidence to show that the interest rate regime adopted by the monetary authority plays an important role in determining the effectiveness of the transmission mechanism of monetary policy via bank lending channel using Malaysian data. As part of the strategy to deal with the recent financial crisis, the Malaysian government introduced capital control measures which subsequently led to a structural shift in interest rates. Before the shift, interest rates were relatively high. The contractionary monetary policy achieved desirable results through the bank lending channel. However, responses of bank lending to interest rate changes were limited after the structural shift which characterises a period of low interest rate regime, rendering the bank lending channel ineffective.